2018
DOI: 10.3390/pharmaceutics10040238
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Biomimetic Formulation of Clofazimine Hydrochloride Microcrystals for Parenteral Administration

Abstract: Clofazimine (CFZ) is a broad spectrum antimycobacterial agent recommended by the World Health Organization as a first line treatment for leprosy and second line treatment for multidrug resistant tuberculosis. Oral administration of CFZ leads to a red skin pigmentation side effect. Since CFZ is a weakly basic, red phenazine dye, the skin pigmentation side effect results from lipophilic partitioning of the circulating, free base (neutral) form of CFZ into the skin. Here, we developed a stable and biocompatible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…The weakly dibasic (pK a 3.83, 7.54 at 37 °C, I = 0.15 M [105]) phenazine antibiotic (M W 473.4 g/mol) is used to treat leprosy. The orally-bioavailable molecule has the very unusual characteristic of precipitating and accumulating as easily-visible red microcrystals in macrophages [119]. Figure 5 shows the distribution of properties used by Lipinski et al [120] to define the Rule of 5 as an indicator of "drug-likeness."…”
Section: Physicochemical Properties Of Database Moleculesmentioning
confidence: 99%
“…The weakly dibasic (pK a 3.83, 7.54 at 37 °C, I = 0.15 M [105]) phenazine antibiotic (M W 473.4 g/mol) is used to treat leprosy. The orally-bioavailable molecule has the very unusual characteristic of precipitating and accumulating as easily-visible red microcrystals in macrophages [119]. Figure 5 shows the distribution of properties used by Lipinski et al [120] to define the Rule of 5 as an indicator of "drug-likeness."…”
Section: Physicochemical Properties Of Database Moleculesmentioning
confidence: 99%
“…In this study, we explored the differences in the interaction of clofazimine hydrochloride nanoparticles (CFZ-HCl NPs) [19] with normal and tumor bearing prostates, using the transgenic adenocarcinoma of the mouse prostate (TRAMP) animal model [20]. CFZ is a red-pigmented dye and a weakly basic, FDA-approved, orally administered, antimycobacterial agent that is recommended by the World Health Organization as a treatment for leprosy and multidrug resistant tuberculosis [2129].…”
Section: Introductionmentioning
confidence: 99%
“…In patients, CFZ exhibits atypical pharmacokinetic properties that result in accumulation and stabilization in tissue macrophages of solid drug biocrystals that resemble a hydrochloride (HCl) salt form of the drug [3035]. These CFZ-HCl biocrystals were determined to be biocompatible, stable, long-lived, relatively non-toxic, and anti-inflammatory [36, 37], which led to the development of a biomimetic formulation of CFZ-HCl NPs for parenteral administration [19]. Importantly, Murashov et al demonstrated that these CFZ-HCl NPs preserved the majority of characteristics of CFZ-HCl biocrystals, including targeting and accumulating inside macrophages in vitro and in vivo [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations